Sodium Ions Affect Pyrraline Formation in the Maillard Reaction With Lys-Containing Dipeptides and Tripeptides - Liang, Zhili; Chen, Xu; Yang, Zhao; Liu, Yan; Qiu, Xueying; Zeng, Zhenzhen; Lu, Shuidi; Liu, Yuehan (Frontiers in Nutrition, 2022)
Advanced glycation end products (AGEs) are potentially-hazardous chemical compounds, produced by the Maillard reaction between reducing sugars and Lysine side-chain amino groups in proteins. AGEs are strongly associated with diabetes, Alzheimer's disease and atherosclerosis. Pyrraline, a sugar derivative of Lysine, is a major AGE and an established marker for the presence of dietary AGEs. In this study, the effects of NaCl and different dipeptide and tripeptide structures were compared on the formation of pyrraline-containing peptides and the glucose derivative 3-deoxyglucosone in the presence of glucose and at different NaCl concentrations. The physicochemical properties (polarizability, dipole moment, molecular volume and dissociation constant) and the thermodynamic properties of the peptides were determined. The amount of the pyrraline decreased significantly in the following order of peptides (at the same concentrations): Lys-Phe > Lys-Ala > Lys-Gly; Lys-Gly-Phe > Lys-Gly-Ala > Lys-Gly-Gly. The highest levels of both pyrraline and 3-deoxyglucosone occurred at 0.2 mol/L Na+. Sodium ions appear to alter the intramolecular electron density and charge distribution of the peptides and facilitate the reaction by stabilizing some of the intermediates in the reaction sequence.